Enantioselective Synthesis of (R)-Tiagabine via Asymmetric Hydrogen Atom Transfer Protocol - Li, Longfei; Chen, Wanjiao; Xu, Zhongyun; Jiang, Jie; Zhang, Yong-Qiang (Synthesis, 2023)
An enantioselective synthesis of tiagabine has been achieved utilizing an asymmetric hydrogen atom transfer protocol to construct its essential chiral tertiary carbon center. A cyclization reaction via double N-substitution is tactically orchestrated as the other key step to install the crucial alkaloid ring. Compared with the previous synthetic strategy, which used commercially available nicotinate as the starting material to ensure a short synthetic route, this strategy uses a readily modifiable and accessible alkyl-substituted acrylate as the starting material and thus provides a scenario for the facile synthesis of analogues and derivatives of tiagabine for further biological research.
Keywords: analogue synthesis; chiral tertiary center; enantioselective; hydrogen atom transfer; tiagabine; titanium catalysis